INTERNATIONAL CULTURAL FIESTA: PROMOTING UNDERSTANDING OF DIVERSE CULTURES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, PENANG, 5 April 2015 The International Cultural Fiesta 2015 (ICF 2015), themed “Mystique Rhythm” was an initiative by Universiti Sains Malaysia (USM) to promote the diverse cultures from various nations to impart a better understanding on internationalisation to the campus community.